Heat transfer performance of single and hybrid water-based nanofluids (Al2O3 and SiO2) in nucleate pool boiling - Muhamad Hadie Aizzat, Asli (2020)
Enhancement of heat transfer performance in nucleate boiling has become one of the prominent topics due to the demand of high cooling density in industry applications. Recently, various types of nanofluids have been researched in terms of their cooling performance in the multiphase system. For instance, Al2O3 nanofluids gave a completely different Heat Transfer Coefficient (HTC) performance compared to SiO2 nanofluids in various concentration levels. The reasons of the inconsistencies are still elusive. In addition, the HTC performances of those single nanofluids in steady state conditions have not been well reported in literature. The present work aims to evaluate the HTC performance, the steady state conditions, and the relation between surface properties towards the HTC of Al2O3 and SiO2 nanofluids in saturated pool boiling of single and hybrid Al2O3/SiO2 water-based nanofluids. Two types of single nanofluid dispersions (Al2O3 and SiO2) were prepared. Their hybrid nanofluids were mixed in different volume concentration ratios of 0:100, 25:75, 50:50, 75:25, and 100:0 percent to achieve three final concentrations of C = 0.001 vol. %, 0.01 vol. %, 0.025 vol. %. Later, experiments were conducted to obtain the heat transfer coefficients (HTCs) and steady state conditions of the HTC within a prescribed time, as well as evaluation of surface roughness properties. The present work demonstrated the HTC values for single and hybrid nanofluids in a series of time variation of wall superheat, ΔTw. Next, considering the significance of the clarification of heat transfer steadiness in the system , experiment for the quasi steady state was extended up to 5 hours to reveal the dependencies of HTC over time in single and hybrid nanofluids with low concentration C = 0.001 vol. %. Finally, due to the occurrence of nanoparticle deposition in the present experiment, surface roughness measurements were conducted to investigate the surface structure evolution with respect to the boiling time in nanofluids using SiO2 and Al2O3 nanofluids of low concentration C = 0.001 vol. %. The HTC results were found to enhance considerably for Al2O3 and on the contrary, deteriorate for SiO2 nanofluids. Notably, for the hybrid nanofluids (Al2O3/SiO2: 50/50 vol. %), the HTCs were dramatically enhanced at the initial stage after 5 seconds, whilst slowly deteriorated once the time variation increased up to ΔTw = 16 °C, especially in a higher ratio of SiO2 nanofluids. In addition, it should be noted that the HTC performance of hybrid nanofluids was found to be in between those of Al2O3 and SiO2 in the time variation of 1 hour. For the single and hybrid nanofluids in low concentration, SiO2 nanofluids achieved the steady state conditions after 5 hours at 17 °C except for single Al2O3 nanofluids which did not achieve steady state condition even after 5 hours with a slight gradual increase with respect to the time variation of wall superheat (ΔTw). Meanwhile, the surface roughness of heater surface, Ra values were 1.7995 µm for Al2O3 and 1.7507 µm for SiO2 after boiling in nanofluids. However, the HTC values were different where they increased in Al2O3 nanofluids but deteriorated for SiO2 nanofluids. The surface roughness results of heater surface for both nanofluids were nearly the same but different HTC performances were reported. Therefore, surface roughness was not a significant factor to the HTC performance in the present work.